2023
DOI: 10.3390/batteries9060315
|View full text |Cite
|
Sign up to set email alerts
|

A Novel BC2N Monolayer as Anode Material for Li-Ion Battery

Abstract: The stability, mechanical and electronic properties of a BC2N monolayer and its potential use as an anode material for Li-ion batteries were explored using the density functional theory calculation. The proposed BC2N monolayer shows good thermal and dynamical stabilities, as indicated by the ab initio molecular dynamics simulations and phonon dispersion calculations. The BC2N monolayer exhibits highly anisotropic mechanical properties. The electronic structure calculation based on the hybrid functional suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In contrast to T-graphene, which exhibits metallic behavior [31], the T-graphene like BC 2 N monolayer behaves as a semiconductor. Previous theoretical work suggests that the primary contribution to the density of states in the conduction and valence bands of BC 2 N comes from the p orbitals of B and C atoms [22]. However, upon the adsorption of Na/K atoms, the electronic state of BC 2 N transitions into a metallic state.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast to T-graphene, which exhibits metallic behavior [31], the T-graphene like BC 2 N monolayer behaves as a semiconductor. Previous theoretical work suggests that the primary contribution to the density of states in the conduction and valence bands of BC 2 N comes from the p orbitals of B and C atoms [22]. However, upon the adsorption of Na/K atoms, the electronic state of BC 2 N transitions into a metallic state.…”
Section: Resultsmentioning
confidence: 98%
“…In recent studies, T-graphene, a carbon monolayer consisting of flat structures incorporating both C8 and C4 rings, has been predicted to be a potential candidate as alkali-ions batteries anode [20,21]. The theoretical studies propose that the incorporation of N and B atoms into T-graphene can lead to the formation of a B-C-N nanosheet that exhibits a stable T-graphene-like structure [22,23]. Recent studies suggested that T-graphene like BC 2 N is a promising material for use in lithium-ion batteries as an anode [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…91 The gravimetric capacity of Li is also higher than those of other 2D materials such as graphene (744 mA h g −1 ), 81 g-borocarbonitrides (710 mA h g −1 ), 95 g-C 3 N 4 (943 mA h g −1 ), 96 and T-graphene (876.55 mA h g −1 ) 97 and comparable to those of the carbonbased biphenylene monolayer (1075.37 mA h g −1 ) 54 and BC 2 N monolayer (1098 mA h g −1 ). 98 Similarly, the storage capacity of bpn-BCN for Na and K is slightly lower than that of the previously reported carbon biphenylene monolayer for Na and K. 99,100 To assess the impact of alkali metal atom adsorption on the volume change of the bpn-BCN monolayer, we investigated the in-plane expansion of the bpn-BCN single layer. As expected, the lattice parameter increases with increasing M adsorption.…”
Section: η-Bcn As An Anode Materials For Alkali Metal Ion Batteriesmentioning
confidence: 94%